Epidemiology and clinical profile of cleft lip and palate patients, in a tertiary institute in Punjab, India: A preliminary study - Sanjeev K Uppal; Sheerin Shah; Rajinder K Mittal; Ramneesh Garg; Ashok Gupta (Wolters Kluwer Medknow Publications, 2016)
Objective: The purpose of this study was to report the epidemiological profile and surgeries done on patients with cleft lip and palate from August 2007 to December 2014. Materials and Methods: A retrospective study was done to evaluate the patients operated for either cleft lip (with or without alveolus), cleft palate or secondary correction. The age of operative intervention, sex distribution, type of cleft, laterality, type of surgery, and duration of stay were reported. Results: A total of 411 cleft patients were seen during this period (August 2007-December 2014). Among this 36 (8.7%) patients had an incomplete cleft lip, 57 (13.9%) had a complete cleft lip, and 29 (7%) had cleft lip with alveolus. Isolated cleft palate was seen in 104 (25%) patients and cleft lip and palate were seen in 185 (45%) patients. Eighty percentage patients were aware of the surgeries for cleft lip and palate by various hospital communications. The mean age of patients operated for cleft lip was 5.3 months and Randall Tennison modified repair was done in 88% of these patients. The mean age of patients undergoing palatoplasty was 1.6 years and the most common surgery done was pushback palatoplasty with intervelar veloplasty (73.6%). Seventy-six patients underwent a secondary correction, out of which 30 patients got lip revision and 26 got fistula repair. A total of 15 patients had other associated anomalies. The average duration of stay in hospital for a cheiloplasty patient was 7 days, of palatoplasty was 8 days and of secondary surgery was 5 days. Conclusion: This study indicates that cleft lip and palate are most common types of cleft predominantly on the left side and males being more. Newspapers, various medical institutions, and media are useful measures to spread public awareness about early surgery, follow-up, secondary corrective surgeries, speech and dental therapy. Early diagnosis and appropriate timings of these surgeries produce satisfactory results with minimal morbidity.